Prevalence, Costs and Consequences of "Manovra AIFA" for ICS-LABA Treatment in Patients with Asthma or COPD: A Real-Practice Analysis. Issue 3 (November 2016) - Bettiol, Alessandra; Bolcato, Jenny; Pirolo, Roberta; Franchin, Giulia; Deambrosis, Paola; Giusti, Pietro; Chinellato, Alessandro
Introduction: The pharmaceutical respiratory market represents a growing expenditure for the National Healthcare System (NHS), mainly due to the increasing use of corticosteroid + long-acting β2 agonist (ICS-LABA) associations. Following a supplementary budget program ("manovra AIFA", MA) in 2015, a reduction in drug costing was put in place which resulted in a de facto reduction in price and/or in a pay back provision (2015-2017). This study aimed to evaluate the impact of MA on ICS-LABA and on total direct respiratory costs for ICS-LABA-treated patients. Methods: A retrospective study conducted in the Local Health Authority of Treviso identified users of ICS-LABA in 2014. Patients with asthma or COPD were separately analyzed, according to patient exemptions. The expenditure for ICS-LABA and its variation following the MA were assessed; total direct respiratory costs were also calculated. Results: ICS-LABA users were 9, 017 and 41.18% of them had an exemption for asthma or COPD. Considering dual-indication ICS-LABA medications, the total annual cost was €842, 234; after the MA, this expenditure will probably be reduced by 8.2%. Costs were higher in COPD patients compared to patients with asthma (€2, 268.97 vs. €535.77 per patient/year), due to more frequent hospitalizations (22.0% vs. 2.9%). For patients with asthma, pharmaceutical treatment costs were the most expensive (78.4% of total costs). Discussion and conclusions: A reduction in costs for respiratory medications occurred following the MA, but real savings for the NHS are difficult to estimate, due to the variability in delivery volume and in the consequent pay back quantification.